(untitled) (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Saputra FR, Wahid I, Supriyono, Hadi UK. 2025. Abundance of adult Aedes aegypti and Aedes albopictus (Diptera: Culicidae) across six settlements in South Sulawesi, Indonesia. Biodiversitas 26: 509-519. Aedes aegypti and Ae. albopictus are major vectors of dengue, chikungunya, and Zika. These diseases impose a significant global health burden, particularly in tropical and subtropical regions where environmental conditions favor mosquito population growth and disease transmission. This study aimed to analyze the abundance of adult Ae. aegypti and Ae. albopictus across six settlements in South Sulawesi Province, Indonesia. Mosquito collections were conducted from January to October 2023. The selected settlements were Manuju, Pangembang, Tamala’lang, Adatongeng, Lae-Lae, and Panaikang. The findings indicated that Ae. aegypti was predominantly found indoors in Lae-Lae, with a total of 696 individuals (58.7%) from 100 surveyed houses, while Ae. albopictus was mostly found indoors in Pangembang, with 31 individuals (55.4%). Outdoors, Ae. aegypti was most abundant in Lae-Lae, where 32 individuals (80.0%) were captured in vegetated areas around 100 surveyed houses, such as near bamboo trees and other vegetation surrounding the settlements Similarly, Ae. albopictus was more frequently found outdoors in the same area, with 177 individuals (33.1%) captured under similar conditions. In total, Ae. aegypti was primarily found indoors, with 1186 individuals (p<0.01), while Ae. albopictus was mainly found outdoors, with 535 individuals (p<0.001). These findings reveal significant differences in the abundance of these mosquito species between indoors and outdoors, highlighting the influence of local environmental factors on their distribution in South Sulawesi Province, Indonesia.